DETERMINATION OF PHYSICAL EQUATIONS USED IN PROCESS INDUSTRIES USING DIMENSIONAL ANALYSIS - Florin CIOFU (Fiabilitate şi Durabilitate, 2018)
Technological process, however complex, can be broken down into a succession of distinct component processes, in which the input materials undergo changes in shape (mechanical processes), pressure, temperature, concentration, state of aggregation (physical processes) or structure molecular (chemical and biochemical processes). The unitary operations of most process phases in process industries are based on three fundamental processes: pulse transfer, heat transfer, and mass transfer.